Analisis Efisiensi Teknis dan Gap Teknologi pada Produksi Rumput Laut di Jawa Timur Indonesia Menggunakan Metafrontier DEA - Anam, M. Khairul; Albab, M. Ulul; Setyana, Sukma Febri; Prihantini, Campina Illa (Universitas Galuh, 2025)
Seaweed production often experiences fluctuations, with one of the recurring challenges faced by farmers being the suboptimal utilization of available production factors, which in turn impacts production output. The aim of this study is to analyze the level of technical efficiency and the technology gap in seaweed production across three districts in East Java: Sumenep, Banyuwangi, and Situbondo. This research utilizes primary data in a cross-sectional format during the 2023/2024 seaweed cultivation season in the aforementioned districts. A structured questionnaire was used to collect data on the inputs and outputs used in production. The Meta-Frontier Data Envelopment Analysis (DEA) method was applied to measure the technical efficiency of seaweed production in each research area. Based on the results of the technical efficiency analysis, the areas with efficiency scores of 1 (fully efficient) were as follows: Sumenep District (63.33%), Banyuwangi District (40%), and Situbondo District (23.33%). More than 50% of the Decision-Making Units (DMUs) in Sumenep have achieved perfect efficiency (TE = 1), whereas the other two districts have not reached 50% efficiency among their DMUs. Furthermore, the average technical efficiency across the DMUs in the three study locations is 85.3%, indicating that these DMUs can still improve their technical efficiency by up to 14.7%. The average Total Gap Ratio (TGR) shows low variability, although differences still exist. This suggests that the three study areas implement varying production practices, methods, and have different resource availability. However, Banyuwangi District has the highest TGR value among the three study locations, approaching the threshold of 1. This indicates a relatively low technology gap in this area.